FORMATION AND DEVELOPMENT STAGES OF THE PROACTIVE SERVICE CONCEPT IN LABOR RELATIONS - Yusupova , Dinara (GLOBAL SCIENTIFIC CONFERENCE ON MULTIDISCIPLINARY RESEARCH, 2026)
This thesis examines the formation and developmental stages of the proactive service concept in labor relations based on empirical observations and scientific literature. The study analyzes the transition of service systems from a reactive model to a proactive model from an evolutionary perspective. Additionally, it explores the impact of modern digital technologies and data-driven management approaches on this process.